From normative towards positive epistemology: Problem of scientific fact - Brdar Milan (Sociološki Pregled, 2009)
In this article author provides a sketch of a twist from normative towards descriptive epistemology as a result of transformation of contemporary philosophy during the main occurrence known as Linguistic Turn. Best illustrations for epistemic twist are given in theories of Karl Popper, Ludwik Fleck and Thomas Kuhn. These three theories determined deconstruction of traditional philosophy of science and traditional picture of science and its practice. At the same time U isti mah, by the same twist towards descriptive and historical epistemology some core problems of epistemology and methodology are actualized in very sharper form. This concerns mainly of the problems of scientific statements and procedures of establishing of their objectivity and truthfulness. For in all three theories, of Popper, Fleck and Kuhn, empirical statements are functions/dependent of: theoretical framework, of though style or of paradigm, problem of truthfulness ad objective justification shows itself within Minhausen trilema. Task of positive epistemology is not to prescribe some procedure, but to provide reconstruction of real procedures given in practice of scientific communities. That means to show how they resolve problem of epistemic foundation of their theories and how they provide justified reasons to defend their theories as truthful and objective. .